2005
DOI: 10.1111/j.1365-3083.2005.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Anti‐Oxidants on Apoptosis of a Human Polyclonal T‐Cell Line, MT‐2, Induced by an Asbestos, Chrysotile‐A

Abstract: To clarify the effects of silica and silicates on cellular features of lymphocytes, a human T-lymphotropic virus type-1-immortalized polyclonal T-cell line, MT-2, was exposed to various concentrations of chrysotile-A, an asbestos classified as silicate. MT-2 cells underwent apoptosis in a dose-and time-dependent manner. The mitochondrial apoptotic pathway was activated during chrysotile-A-induced apoptosis of MT-2 cells, because of the phosphorylation of JNK and p38, increase of BAX and release of cytochrome-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…We also found that asbestos polyclonally activated CD4-positive T cells and caused activation-induced cell death (5)(6)(7)(8)(9). In addition, PBMCs from healthy donors exposed to asbestos in culture underwent apoptosis (5)(6)(7)(8).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…We also found that asbestos polyclonally activated CD4-positive T cells and caused activation-induced cell death (5)(6)(7)(8)(9). In addition, PBMCs from healthy donors exposed to asbestos in culture underwent apoptosis (5)(6)(7)(8).…”
mentioning
confidence: 78%
“…An HTLV-I-immortalized human polyclonal T cell line, MT-2 (17), was maintained in suspension in RPMI 1640 medium supplemented with 10% fetal bovine serum plus antibodies at 37°C in a humidified atmosphere (9)(10). The UICC (the International Union against Cancer) standard CB sample was kindly provided by the Department of Occupational Health, National Institute for Occupational Health, South Africa (18).…”
Section: Cell Line Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon short-term, high-level exposure to chrysotile, MT-2 cells underwent apoptosis with the production of ROS via the activation of the mitochondrial apoptotic pathway with the phosphorylation of p38 mitogen-activated protein kinase (MAPK) and c-Jun Nterminal kinase (JNK) signaling molecules, resulting in a shiftof the Bax-dominant Bax/Bcl-2 balance, the release of cytochromec from mitochondria into cytosol, and the activation of caspases 9 and 3 as shown on the left side of Fig. 2 and as previously reported (69).…”
Section: Immunological Effects Of Chrysotile Asbestosmentioning
confidence: 61%
“…The MT-2 cell sub-lines CA1-3, CB1-3 and CR were established after continuous exposure to three kinds of asbestos, namely, chrysotile A, chrysotile B or crocidolite, respectively (Hyodoh et al 2005;Miura et al 2006;Maeda et al 2011Maeda et al , 2012. Those established sub-lines exhibited reduced apoptotic fractions when exposed to CA, CB or CR at a high concentration.…”
Section: Expression Of Foxo1 Mrna and Foxo1 Proteinmentioning
confidence: 99%